COMPARISON BETWEEN PAPER-BASED AND WEB- BASED TEST IN THE CLINICAL SKILLS LABORATORY OF UNDERGRADUATE STUDENTS - Doni Widyandana (Asosiasi Institusi Pendidikan Kedokteran Indonesia, 2019)
Background: E-Learning or web-based technology can be used to train undergraduate medical students’ clinicalreasoning skills. Currently, many learning methods are being developed using web-based environment to replacepaper-based because they are more efficient in terms of paper usage and are flexible for a student in accessingmaterials. This study aims to explore student’s working durationaccess time and scores upon the usage of webbasedtest, to compare students’ scores to paper-based test scores, to explore the advantages anddisadvantages, andsuggestions to improve the web-based learning method.Method: This study randomly enlisted 60 medical students of Universitas Gadjah Mada, Yogyakarta, Indonesiaand divided them into web-based (n = 30) and paper- based test (n = 30) groups. Students answered 15 disastermanagement questions and completed a questionnaire. The scores and times needed to answer the questions werecompared using the Mann-Whitney and Independent Sample tests.Results: The duration to answer in the web-based group was shorter than in paper- based group (p = 0.001), butthe average scores difference was not significant (p = 0.169). In the web-based group, similar numbers of studentsaccessed the website during and after working hours. Survey questionnaire results showed that most students realizedthe advantages of this program and gave appropriate suggestions.Conclusion: Practicing clinical reasoning skills using web-based learning method is more time-efficient comparedto the paper-based test. Its high-accessibility improves the learning interest and motivation of the student, with anequal outcome to the paper-based test.